Low physical fitness is a strong predictor of health problems among young men: a follow-up study of 1411 male conscripts - Taanila Henri; Hemminki Antti JM; Suni Jaana H; Pihlajamäki Harri; Parkkari Jari (BMC, 2011)
Abstract Background Military service in Finland is compulsory for male citizens and annually about 90% of 19-year-old men enter into the service. Approximately 15% of them are discharged due to medical reasons constituting a group of young men who are at risk of being marginalised in society. The purpose of the study was to evaluate predictive associations between medical discharge from the compulsory military service and various intrinsic risk factors, including socio-economic, health, health behavior, and physical fitness outcomes. Methods We followed four successive cohorts of conscripts who formed a representative sample of Finnish young men (18-28 years old, median age 19 yrs) for 6 months. To exclude injuries and illnesses originating before the onset of service, conscripts discharged from the service at the medical screenings during the 2-week run-in period were excluded from the analyses. Data regarding medical discharge were charted from computerised patient records. Predictive associations between medical discharge and intrinsic risk factors were examined using multivariate Cox's proportional hazard models. Results Of 1411 participants, 9.4% (n = 133) were discharged prematurely for medical reasons, mainly musculoskeletal (44%, n = 59) and mental and behavioral (29%, n = 39) disorders. Low levels of physical fitness assessed with a 12-min running test (hazard ratio [HR] 3.3; 95% confidence interval [CI]: 1.7-6.4), poor school success (HR 4.6; 95% CI: 2.0-11.0), poor self-assessed health (HR 2.8; 95% CI: 1.6-5.2), and not belonging to a sports club (HR 4.9; 95% CI: 1.2-11.6) were most strongly associated with medical discharge in a graded manner. The present results highlight the need for an improved pre-enlistment examination and provide a new means of identifying young persons with a high risk for discharge. Conclusions The majority of the observed risk factors are modifiable. Thus preventive measures and programs could be implemented. The findings suggest that increasing both aerobic and muscular fitness is a desirable goal in a pre-training program before entering military service. Attention to appropriate waist circumference and strategies addressing psychological well-being may strengthen the preventive program. Optimally the effectiveness of these programs should be tested in randomized controlled intervention studies.